Clinical risk factors and prognostic model for idiopathic inflammatory demyelinating diseases after haploidentical hematopoietic stem cell transplantation in patients with hematological malignancies. Issue 11 (17th August 2021) - Deng, Rui‐Xin; Wu, Ye‐Jun; Xu, Lan‐Ping; Liu, Kai‐Yan; Huang, Xiao‐Jun; Zhang, Xiao‐Hui
Abstract: Idiopathic inflammatory demyelinating diseases (IIDDs) of the central nervous system (CNS) are rare but serious neurological complications of haploidentical hematopoietic stem cell transplantation (haplo‐HSCT). However, the risk factors and a method to predict the prognosis of post‐transplantation CNS IIDDs are not available. This retrospective study first reviewed data from 4532 patients who received haplo‐HSCT during 2008–2019 in our center, and 184 patients (4.1%) with IIDDs after haplo‐HSCT were identified. Grades II to IV acute graft‐versus‐host disease (aGVHD) ( p < 0.001) and chronic GVHD (cGVHD) ( p = 0.009) were identified as risk factors for developing IIDDs after haplo‐HSCT. We then divided the 184 IIDD patients into a derivation cohort and validation cohort due to transplantation time to develop and validate a model for predicting the prognosis of IIDDs. In the multivariate analysis of the derivation cohort, four candidate predictors were entered into the final prognostic model: cytomegalovirus (CMV) infection, Epstein–Barr virus (EBV) infection, IgG synthesis (IgG‐syn) and spinal cord lesions. The prognostic model had an area under the receiver operating characteristic curve of 0.864 (95% CI: 0.803–0.925) in the internal validation cohort and 0.871 (95% CI: 0.806–0.931) in the external validation cohort. The calibration plots showed a high agreement between the predicted and observed outcomes. Decision curve analysis indicated that IIDD patients could benefit from the clinical application of the prognostic model. The identification of IIDD patients after allo‐HSCT who have a poor prognosis might allow timely treatment and improve patient survival and outcomes.